CLASSIFICATION OF VIOLATIONS OF THE FIRST BASIC LOGIC PRINCIPLE: JUDICIAL, MANIPULATIVE AND COMIC EFFECTS - Nevelska-Hordieieva , Olena; Panova , Maryna; Voitenko , Dmitry; Melikhova, Yuliia (Revista Inclusiones, 2020)
The articleanalyzes common logical mistakes associated with violation of the fundamental law of logic -the principle of identity. These mistakes are associated with the peculiarities of concepts and judgments, with the rules of the logical operation of definition, with the mistakes of proof: a strawmanfallacy (in Latin: ignoratio elenchi), and withthe removal of a phrase from the context. Mistakes associated with violation of the principle of identity, lead to violations of the construction and understanding of the text, reduce the culture of speech. They are also used to manipulate the consciousness of people or to create a comic effect. The purpose of the work is to consider possible violations of the principle of identity, to build a classification of the identified mistakes, to study their causes and consequences. Violations of the first fundamental law of logic can be caused by various reasons, such as the replacement of one concept by another, the equalization of concepts with different meanings, changing the content of the original concept, changing the meaning of a phrase, the substitution of a thesis, etc. Four types of violations of the first basic principle of logichave been identified: 1) properties of concepts, 2) features of the text, 3) properties of thinking, 4) psychological personal reasons